Distal pancreatectomy for pancreatic carcinoma in the era of multimodal treatment. Issue 3 (22nd December 2014) - Paye, F; Micelli Lupinacci, R; Bachellier, P; Boher, J -M; Delpero, J -R
Abstract: Background: Recent publications have suggested improvements in the outcome of distal pancreatectomy (DP) for cancer, but the series were small and heterogeneous. The aim of the present study was to assess perioperative and long-term outcomes of DP for pancreatic adenocarcinoma in the era of multimodal treatment in a major European country. Methods: This was a nationwide study of all patients undergoing DP for pancreatic adenocarcinoma between 2004 and 2009 in 28 centres in France. Postoperative and long-term outcomes were assessed retrospectively and outcome predictors were explored by multivariable analysis. Results: A total of 278 patients were enrolled. Multivisceral resections were performed in 58 patients (20·9 per cent), venous resections in 33 (11·9 per cent) and arterial resections in 11 (4·0 per cent). Neoadjuvant chemoradiotherapy was used in 20 patients. Postoperative complications occurred in 96 patients (34·5 per cent) and pancreatic fistulas developed in 76 (27·3 per cent). The postoperative 90-day mortality rate was 5·0 per cent. In univariable analysis, multivisceral resection was the only factor associated with postoperative morbidity ( P = 0·048). Age 65 years or less, body mass index of at least 30 kg/m 2 and absence of preoperative chemoradiotherapy were associated with an increased risk of pancreatic fistula in multivariable analysis. Overall survival rates at 3 and 5 years were 44·9 and 29·5 per cent respectively. In multivariable analysis, only the presence of lymph node metastases was associated with poorer overall survival. Conclusion: Postoperative morbidity and mortality associated with pancreatic fistula remain considerable after DP, but both short- and long-term survival have improved markedly. Abstract : Outcomes improved in this millennium